(untitled) (Journal of Economic Research & Business Administration, 2015)
In article opportunity and need of application of the Internet for market researches is considered. Information technology hasn’t played before such an important role in the success of the business and didn’t make an impact on all the activities . Internet use concerns today almost all aspects of marketing activities of many enterprises where its role permanently increases. The purpose of the real research was use of a computer network the Internet in market researches of the enterprise. For this purpose authors studied theoretical approaches to determination of a role of information in decision-making process, aspects of application of information technologies and market researches in enterprise operation are considered. A row of recommendations, including creation the Internet -shop for the purpose of improving of its operation is offered a manual of the analysable company.